Potential biological control agents of Zeugodacus cucurbitae (Coquillett): A review. (22nd June 2022) - Diksha,; Mahajan, Evani; Singh, Sumit; Sohal, Satwinder Kaur
Abstract: Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) is a serious agro‐economic pest of cucurbits around the world. Management of tephritid fruit flies is till date mainly dependent on the use of chemical pesticides. In a rising concern about environment quality and rapid development of resistance in insect pests, biological control of insect pests is being contemplated, and in response, research approaches are constantly evolving. Various naturally occurring control agents of melon fruit fly such as parasitoids, bacteria, fungi and nematodes have potential in the management of Z. cucurbitae . Many parasitoids including Psyttalia fletcheri, Fopius arisanus, Dirhinus giffardii and Spalangia endius are known to attack various life stages of Z. cucurbitae . Although parasitoids are being principally exploited for control of Z. cucurbitae, various other entomopathogens such as fungi ( Beauveria bassiana, Paecilomyces fumosoroseus, Metarhizium anisopliae ), bacteria ( Bacillus thuringiensis ), nematodes ( Heterorhabditis indica, Steinernema feltiae ) and microbial toxins/products (spinosad, avermectin) are being investigated or used for biological control. The development of farming methodologies with greater credence on ecosystem services such as biological control of Z. cucurbitae will increase sustainability of agroecosystems. This review provides a concise compilation of these biological control agents along with their effectiveness and will help researchers in designing various integrated pest management strategies against Z. cucurbitae that involve biological control agents.